2016
DOI: 10.1111/1475-6773.12610
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physician Practice Patterns after Implementation of a Communication‐and‐Resolution Program

Abstract: Objective. To test if a 2006 communication-and-resolution program to address unexpected adverse outcomes was associated with changes in cost and use trajectories. Data Source. Records of patients discharged with a principal diagnosis of chest pain from 44 nonfederal general hospitals in Cook County, Illinois, between January 2002 and December 2009. Study Design. Propensity-score matched discharges from the intervention and comparison hospitals before computing difference-in-differences estimates of quarterly g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…16,17 This can improve quality of care. Helmchen et al 24 demonstrated a decrease ordering of lab tests and imaging, suggesting that CRP may decrease the practice of defensive medicine. The finding in the current study demonstrating a decrease time to resolve a case and the significant percent of cases that were resolved by apology alone supports the conclusions of Kass et al 25 that CRP mitigates the stress of litigation on patients and physicians compared to deny and defend.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 This can improve quality of care. Helmchen et al 24 demonstrated a decrease ordering of lab tests and imaging, suggesting that CRP may decrease the practice of defensive medicine. The finding in the current study demonstrating a decrease time to resolve a case and the significant percent of cases that were resolved by apology alone supports the conclusions of Kass et al 25 that CRP mitigates the stress of litigation on patients and physicians compared to deny and defend.…”
Section: Resultsmentioning
confidence: 99%
“…Data on written complaints in the National Health Service in the UK (2016–2017) showed that the largest proportion of complaints was attributed to communication issues. The communication‐and‐resolutions program in the USA aims to promptly offer financial and non‐financial resolution when adverse events are caused by substandard care. Patient and family involvement is extensive and integral to this program.…”
Section: Discussionmentioning
confidence: 99%
“…Patient and family involvement is extensive and integral to this program. A study by the University of Illinois found that by encouraging transparency and taking a proactive approach with patient engagement, the communication‐and‐resolutions program may help to resolve malpractice disputes faster and at a lower cost. By enhancing the quality of communication with parents through engaging them in the process of the review, there is potential to reduce the number of complaints or amount of litigation.…”
Section: Discussionmentioning
confidence: 99%
“…Helmchen et al. further report about changes in physician practice patterns after UIC's implementation of the Seven Pillars program (Helmchen, Lambert, and McDonald ). Gallagher et al.…”
Section: Contents Of This Special Issuementioning
confidence: 99%